Food safety risk assessment and countermeasures in China based on risk matrix method - Yu, Huiqin; Song, Yinghua; Lv, Wei; Liu, Dan; Huang, Haining (Frontiers in Sustainable Food Systems, 2024)
Background Food safety has always been a major concern for people, and frequent food safety incidents pose a serious threat to people’s health and safety. To identify high-risk patterns in the field of food safety and assist regulatory authorities in scientifically managing food safety risks, this study aims to evaluate food safety risks from multiple dimensions and provide a scientific basis for formulating targeted food safety management measures. Methods The risk matrix method, along with the Borda method, is used to evaluate food safety risks. Based on the constructed food safety incident database, the risk matrix method is applied for static risk assessment from seven aspects: food categories, years, provinces, incident entities, causes, pollution sources, and links, and for dynamic risk assessment in different provinces. Results The top five food categories in risk ranking are meat and meat products, fruits and vegetables, grain and grain products, other category, and aquatic products. Food safety risks show an increasing trend year by year, with the years 2006, 2012-2015 and 2019 having higher risk rankings. The top three provinces in risk ranking are Hunan, Guangdong, and Shaanxi. The top four entities in risk ranking are restaurants, enterprises, households, and canteens. The top four causes in risk ranking are human intention, human error, mismanagement, and production and social environment. The top four pollution sources in risk ranking include chemical pollution, other pollution, biological pollution, and food additives. The top three links in risk ranking include production and processing link, catering link, and agricultural production link. Across provinces, food safety risks in the years 2012-2015 are generally higher compared to other years, with the highest number of high-risk provinces in 2014. Implication The findings of this study have significant implications for food safety management in China. By implementing food safety risk prevention and control countermeasures proposed, China can strengthen its food safety management framework, reduce the incidence of food safety incidents, and safeguard the health and well-being of its population.